Repellent and Feeding Deterrent Activities of Butanolides and Lignans Isolated from Cinnamomum camphora against Tribolium castaneum - Yang Wang; Li-Ting Zhang; Di Zhang; Shan-Shan Guo; Chao Xi; Shu-Shan Du (Journal of Chemistry)
Three lignans (1–3) and three butanolides (4–6) were isolated from the lipophilic extract of the Cinnamomum camphora stem bark. The six compounds were identified as (-)-sesamin (1), 9α-hydroxysesamin (2), 9β-hydroxysesamin (3), obtusilactone A (4), isoobtusilactone A (IOA, 5), and isomahubanolide (6) from their spectroscopic data. Four (1, 2 and 5, 6) of them were evaluated for their repellent and feeding deterrent activities against Tribolium castaneum. In this work, the three butanolides (4–6) were confirmed to exist in C. camphora for the first time. Results of bioassays indicated that (-)-sesamin (1), IOA (5), and isomahubanolide (6) displayed certain repellent activities against T. castaneum at 78.63, 15.73, and 3.15 μg/cm2 at 2 h after exposure. Among the three compounds, (-)-sesamin (1) and IOA (5) exerted stronger effects and maintained longer duration of repellency. Furthermore, IOA (5) and isomahubanolide (6) showed good feeding deterrent activity against T. castaneum. IOA (5) was still potently active at low concentrations with the feeding deterrence index (FDI) ranging from 42.85% to 50.66% at 15–1500 ppm. This work provides some evidence for explaining antiinsect properties of the nonvolatile fraction of the C. camphora stem bark and helps promote the development and comprehensive utilization of this tree species.